2008
DOI: 10.1086/592762
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Lived Absorptive Type III–like Microwave Bursts as a Signature of Fragmented Electron Injections

Abstract: In this paper, we devote ourselves to interpreting the short-lived absorptive type IIIYlike microwave bursts in the 2006 December 13 flare event observed with high temporal and spectral resolutions (8 ms and 10 MHz) by the Chinese Solar Broadband Radio Spectrometer (SBRS/Huairou) at 2.6Y3.8 GHz. In the decimeter-centimeter wavelength range, we first present the observations of short-lived bursts represented as a number of absorptive ''spikes'' superposed on the type IV continuum that can be connected by fast-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…(Tan et al 2007(Tan et al , 2010 constant of 2.90 GHz during the type III pairs. This train behaves as absorption structure which is analyzed by Chen & Yan (2008).…”
Section: Several Type III Pair Events In Postflarementioning
confidence: 99%
See 1 more Smart Citation
“…(Tan et al 2007(Tan et al , 2010 constant of 2.90 GHz during the type III pairs. This train behaves as absorption structure which is analyzed by Chen & Yan (2008).…”
Section: Several Type III Pair Events In Postflarementioning
confidence: 99%
“…The RS branches start from 2.95 -2.92 GHz and extend to 3.3 -3.6 GHz with average frequency drift of about 8.6±0.8 GHz s −1 , the burst lifetime is 0.1 -0. constant of 2.90 GHz during the type III pairs. This train behaves as absorption structure which is analyzed by Chen & Yan (2008).…”
Section: Several Type III Pair Events In Postflarementioning
confidence: 99%
“…The maximum absorptive effect occurred at the DPR levels. The parameters of millisecond spikes are determined by small dimensions of the particle beams and local scale heights in the radio source (as Chen and Yan [2008] showed).…”
Section: New Observationmentioning
confidence: 98%
“…Their observational parameters are about 20-60% in absorption depth, $12 GHz s À1 in frequency drift rate, with about 70 MHz instantaneous bandwidth and about 2.5% relative bandwidth. It is suggested that these short-lived absorptive type III-like microwave bursts may be due to fragmented electron injections under the interactions between emerging fluxes and the multiple flare loops, and bi-directional electron beams can be generated near the reconnection region (Chen and Yan, 2008). Some of these beams can propagate upward into the magnetic trap where the continuum emission forms, which then results in the observed absorptive type III-like bursts with negative drift rates.…”
Section: The 13 Dec 2006 Eventmentioning
confidence: 99%
“…The microwave observation shows that the mean frequency drift rate of these starting frequencies is around 60 MHz s À1 , which means that the reconnection region is moving upward, and its velocity can be estimated to be 400 km s À1 . It is natural to believe that such a phenomenon is due to the ascending motion of the emerging fluxes (Chen and Yan, 2008).…”
Section: The 13 Dec 2006 Eventmentioning
confidence: 99%